2005
DOI: 10.1385/bter:108:1-3:053
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Plasma and Hernia Sac Tissue Copper Levels in Direct and Indirect Inguinal Hernia Patients

Abstract: Although the inguinal hernia is among the most commonly encountered and well-described health problems all over the world, the etiology is still controversial. The aim of this study was to compare the plasma and hernia sac tissue copper levels in direct and indirect inguinal hernia patients. Plasma and hernia sac tissue copper levels obtained from patients operated under spinal anesthesia with primary direct (group I, n = 55, 45 male, mean age = 45.68 yr) and indirect (group II, n = 55, 40 male, mean age = 38.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Postoperative body temperature care reduces the effects of low temperature on patient rehabilitation and prognosis, excluding unfavorable factors and promoting patient recovery (18). Various postoperative indicators demonstrated that rehabilitation status of the observation group was significantly better than that of the control group (p<0.01), suggesting that OR care could effectively improve patient rehabilitation and prognosis, which was consistent with relevant studies (19). When comparing the overall quality of life between the observation and control groups, the scores of quality of life and family adaptability and cohesion in the observation group were significantly higher than those in the control group, demonstrating patient improvement in these areas after care was provided (p<0.01).…”
Section: Discussionsupporting
confidence: 87%
“…Postoperative body temperature care reduces the effects of low temperature on patient rehabilitation and prognosis, excluding unfavorable factors and promoting patient recovery (18). Various postoperative indicators demonstrated that rehabilitation status of the observation group was significantly better than that of the control group (p<0.01), suggesting that OR care could effectively improve patient rehabilitation and prognosis, which was consistent with relevant studies (19). When comparing the overall quality of life between the observation and control groups, the scores of quality of life and family adaptability and cohesion in the observation group were significantly higher than those in the control group, demonstrating patient improvement in these areas after care was provided (p<0.01).…”
Section: Discussionsupporting
confidence: 87%
“…Bellon et al [28] demonstrated increased levels of factors that help degradation of collagen as matrix metalloproteinase 2 (MMP-2) and transforming growth factor B1 expression in fascia transversalis of MIH patients compared with patients with LIH or control patients. Abci et al [29] found lower expression of the inhibitor of MMP-2: tissue inhibitor of metalloproteinase-2 in fascia transversalis in patients with MIH compared with those with LIH or control patients and Kayaoglu et al [30] showed lower levels of copper, a cofactor of an enzyme in collagen tissue metabolism, in plasma and in the hernia sac of MIH patients in comparison to LIH patients. A recently published article by Vestergaard et al [31] found that cumulative exposure to daily heavy lifting activities was associated with the risk of LIHs but not with MIH.…”
Section: Discussionmentioning
confidence: 99%
“…The interrelationship between these three factors is not fully established. However, it seems that there is reduced collagen synthesis by the fibroblasts 43,44 , decreased hydroxylation 32 , decreased cross-linking 46,47 and/or increased MMP activity 32,55,65,67,73 , causing accelerated collagen breakdown (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…Lysyl oxidases are copper dependent, and a study of the copper level in plasma and hernia sacs showed that the amount of copper was significantly lower in patients with a direct inguinal hernia than in people with an indirect inguinal hernia, which might reduce the lysyl oxidase activity 46 . The level of lysyl oxidase-like 1 was significantly lower in patients with a direct inguinal hernia than in controls 47 .…”
Section: Stability Of Collagenmentioning
confidence: 99%